Publication and Recognition: Kay Boyle and the O. Henry Award - Christine HAIT (E-REA)
From 1932 until 1981, over the course of nearly fifty years, the judges for the O. Henry Award, an annual American award for outstanding short fiction, frequently recognized Kay Boyle’s stories as exemplary. Two of her stories received the award for best short story of the year: “The White Horses of Vienna” in 1935 and “Defeat” in 1941. Eight other Boyle stories were selected as O. Henry Prize Stories, that is, stories that did not receive the top award but were included in the annual collection. In a list of authors whose work has been included in the annual collections, Boyle shares seventh place with John Cheever, Nancy Hale, and Jean Stafford, who also had ten stories included in the annual collections. In addition, Boyle and Eudora Welty often published stories that competed in the same years for the judges’ attention. The series editors’ Introductions to the collections are a valuable yet overlooked resource for scholars of American short fiction writers, both writers well known today and writers whose reputations have diminished over time. The Introductions offer evidence of Boyle’s influential role as a writer of popular and critically acclaimed short fiction. Knowing the history of the O. Henry Award (including criteria for evaluation, series editors, judges, and winners) and Boyle’s history with the Award helps readers to understand her short story publishing history and to appreciate her career in the context of other writers.